THE UP SLIS ALUMNI: QUO VADIS? - Santos, Yhna Therese P. (Journal of Philippine Librarianship; Vol 35 (2015): A-LIEP 2015 Special Issue, 2016)
This paper examined the career paths chosen by the graduates of the UP School of Library and Information Studies. Using an online survey form, 185 graduates from the UP SLIS indicated their current employment information. It was revealed in the survey that the traditional path of librarianship is still the most common type of employment for SLIS graduates. Most of the respondents indicated that they are from academic libraries and special libraries while some of the graduates also mentioned being employed in the archives and records management sector. The multidisciplinary aspect of the degree also manifested through some of the responses which indicated that graduates who decided to pursue a career other than librarianship end up in a variety of industries, such as IT, business, education, law.
Keywords: tracer study, University of the Philippines School of Library and Information Studies, employment of LIS graduates